ANALISIS KEPUASAN KERJA KARYAWAN TERHADAP KEBIJAKAN PIMPINAN PADA PT. NURSULA INDAH PROPERTY MATARAM NUSA TENGGARA BARAT - NIZAR HAMDI; MUSTAAN MUSTAAN (GANEC SWARA, 2021)
This study entitled "an analysis of employee job satisfaction on leadership policies at PT. Nursula Indah Property. This study aims to determine the level of employee satisfaction on the policies of the leadership of PT. Nursula indah property, in addition to knowing which policies should be changed or maintained by the management of PT. Nursula Indah Property. The research method used is descriptive research, while to analyze the data used qualitative analysis with a Likert scale, where to measure employee job satisfaction used a questionnaire. For the quantitative analysis, the GPA (employee satisfaction index) analysis is used, and uses the formula for stress. Based on the analysis of employee satisfaction, of the eleven policy elements studied, there are three policies that employees feel less satisfied with, namely regarding training, wages, and career planning. Of the eleven elements, there are two elements that employees feel very satisfied, namely regarding recreational policies and complementary compensation. Of the eleven policy elements presented, the policies that need to be changed are about training, wages, and career planning. And policies that need to be maintained are policies on job performance appraisal, discipline, bonuses / incentives, complementary compensation, recreation, work agreements, safety and security, and promotion policies. The results of the frequency distribution of the eleven policy elements studied have reached a weighting scale of 3.34 - 5.00 with very satisfied criteriaThis study entitled "an analysis of employee job satisfaction on leadership policies at PT. Nursula Indah Property. This study aims to determine the level of employee satisfaction on the policies of the leadership of PT. Nursula indah property, in addition to knowing which policies should be changed or maintained by the management of PT. Nursula Indah Property. The research method used is descriptive research, while to analyze the data used qualitative analysis with a Likert scale, where to measure employee job satisfaction used a questionnaire. For the quantitative analysis, the GPA (employee satisfaction index) analysis is used, and uses the formula for stress. Based on the analysis of employee satisfaction, of the eleven policy elements studied, there are three policies that employees feel less satisfied with, namely regarding training, wages, and career planning. Of the eleven elements, there are two elements that employees feel very satisfied, namely regarding recreational policies and complementary compensation. Of the eleven policy elements presented, the policies that need to be changed are about training, wages, and career planning. And policies that need to be maintained are policies on job performance appraisal, discipline, bonuses / incentives, complementary compensation, recreation, work agreements, safety and security, and promotion policies. The results of the frequency distribution of the eleven policy elements studied have reached a weighting scale of 3.34 - 5.00 with very satisfied criteria